“Mixing the Green and the Grey”: how public officials use strategic communication to advance sustainable transport policies in Norwegian medium-sized cities - Mjelde, Hilmar; Tønnesen, Anders (Frontiers in Communication, 2025)
This article fills a gap in existing transport and strategic communication literature by examining the role of public communication as a core component in the design and implementation of large-scale policy packages for urban transport-system development. Using a case-study approach focused on the three Norwegian medium-sized urban regions of Grenland, Haugesund, and Sandefjord, and a multi-method approach combining document analysis and interview data, we investigate how public officials use strategic communication to advance climate-friendly transport policies that are perceived as just and legitimate by local stakeholders. We show that the communication must (1) address tensions between different modes of transport such as car use and public transportation; (2) work to overcome geographic tensions, especially in inter-municipal contexts; and (3) address the temporal dimension of transport transitions, so that individual policy measures appear just, logical, and connected. Based on these findings, we suggest to policymakers how communication strategies can help secure policy legitimacy, reduce resistance, and build momentum for sustainable urban change.